Internationalization and Financial Performance: A success case in Portugal - Teixeira, Nuno; Rafael, Bruno; Pardal, Pedro (My University, 2015)
One of the main characteristics of current business environment is related to internationalization of companies and economies, where competitors from different countries with diverse cultures and production factors, easily clash for a position of supremacy in the markets. Thus, internationalization turned the management of organizations in a more complex act, increasing opportunities but also the risks of the business. As such, this paper aims to reflect on the main issues associated with companies’ internationalization and the impact on their management process, in particular on financial performance and organizational changes. In addition, we intend to conduct a case study of a Portuguese company of information technology industry that through its internationalization strategy, managed in less than a decade, to increment the turnover from 10 million to 60 million euros, becoming one of the largest Portuguese groups in the sector and a worldwide success.